VERMONT STATE PAPERS, BEING A COLLECTION OF RECORDS AND DOCUMENTS, CONNECTED WITH THE ASSUMPTION AND ESTABLISHMENT OF GOVERNMENT BY THE PEOPLE OF VERMONT; TOGETHER WITH THE JOURNAL OF THE COUNCIL OF SAFETY, THE FIRST CONSTITUTION, THE EARLY JOURNALS OF THE GENERAL ASSEMBLY, AND THE LAWS FROM THE YEAR 1779 TO 1786, INCLUSIVE 307 (1823). - (:unkn) unknown (My University, 1779)
Required every listed soldier and other householder to be provided and have in constant readiness: a firearm, blade weapon, gunpowder, bullets, and cleaning equipment.
Keywords: REQUIRED POSSESSION